Was markiert jener? - Magdalena Z. Feret (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
This paper is a study of the meaning and use of the demonstrative jener in the contemporary German. The aim of this paper is to perform a corpus analysis of selected excerpts from texts including noun phrases with the demonstrative jener. All the examples are extracted from online versions of the weekly newspaper „Die Zeit“ published in 2018. The analysis carried out in this article intends to investigate how often and in what sense the demonstrative jener is currently in use.